2001
DOI: 10.1128/aac.45.12.3328-3333.2001
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Maximal Effect Method for In Vitro Synergy between Amoxicillin and Ceftriaxone and between Vancomycin and Ceftriaxone against Enterococcus faecalis and Penicillin-Resistant Streptococcus pneumoniae

Abstract: In the present study we assessed the use of a new in vitro testing method and graphical representation of the results to investigate the potential effectiveness of combinations of amoxicillin (AMZ) plus ceftriaxone (CRO) and of CRO plus vancomycin (VAN) against strains of Streptococcus pneumoniae highly resistant to penicillin and cephalosporins (PRP strains). We used the fractional maximal effect (FME) method of time-kill curves to calculate adequate concentrations of the drugs to be tested rather than relyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The ordinate shows the value of the observed FME for each antibiotic alone (open symbols) or for the combination [FME obs(AϩB) ; shown as closed symbols in A and B and as stars in C]. Values of FME obs(AϩB) that are Ͼ1 denote a synergistic effect; values equal to 1 indicate an additive effect; values of Ͻ1 but higher than FME of the antibiotics alone (FME obs A or FME obsB ) indicate an indifferent effect (a value of Ͻ1 and below FME obsA or FME obsB would indicate an antagonistic effect, which was not observed here) (10). For oritavancin, two ranges of concentrations were examined based on the observation of a bimodal concentration-effect relationship with two successive E max values of Ϫ0.43 log CFU at low (L) and Ϫ3.13 log CFU at high (H) concentrations (see Table 2 in reference 21).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The ordinate shows the value of the observed FME for each antibiotic alone (open symbols) or for the combination [FME obs(AϩB) ; shown as closed symbols in A and B and as stars in C]. Values of FME obs(AϩB) that are Ͼ1 denote a synergistic effect; values equal to 1 indicate an additive effect; values of Ͻ1 but higher than FME of the antibiotics alone (FME obs A or FME obsB ) indicate an indifferent effect (a value of Ͻ1 and below FME obsA or FME obsB would indicate an antagonistic effect, which was not observed here) (10). For oritavancin, two ranges of concentrations were examined based on the observation of a bimodal concentration-effect relationship with two successive E max values of Ϫ0.43 log CFU at low (L) and Ϫ3.13 log CFU at high (H) concentrations (see Table 2 in reference 21).…”
Section: Discussionmentioning
confidence: 99%
“…To this effect, we used the FME method (10,16), focusing on the combinations between rifampin, oritavancin, and moxifloxacin Maximal effects used for calculating concentrations were a 1.72-log and 1.32-log CFU decrease for rifampin and moxifloxacin, respectively (21). As studies with oritavancin alone revealed a bimodal dose-effect relationship (21), we considered for this case two E max values (at 0.43-and 3.13-log reduction), corresponding to the two successive plateaus observed in these experiments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations